2022
DOI: 10.9734/ijpr/2022/v10i230243
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on Melatonin Compound and its Functions in Different Fungi and Plants

Abstract: This study summarizes the importance of melatonin in different plants and fungi. In this review, we discussed the biosynthetic pathway of melatonin, its metabolites, and its oxidative reduction. Melatonin is a molecule derived from tryptophan, with pleiotropic activity. It is present in nearly every organism. Its synthetic course depends on the organism in which it resides. The tryptophan to the melatonin pathway, for example, varies in plants and animals. It is thought that the synthetic mechanism for melaton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…MEL also plays a significant role in the protection of plants from various fungal diseases. The antifungal effects of MEL in plants have been studied in several species, and the results suggest that MEL enhances plant resistance against fungal pathogens [ 134 ]. MEL triggers the production of defense-related compounds, such as phytoalexins, antimicrobial peptides, and pathogenesis-related proteins [ 135 , 136 ].…”
Section: Role Of Mel In the Mitigation Of Biotic Stressesmentioning
confidence: 99%
“…MEL also plays a significant role in the protection of plants from various fungal diseases. The antifungal effects of MEL in plants have been studied in several species, and the results suggest that MEL enhances plant resistance against fungal pathogens [ 134 ]. MEL triggers the production of defense-related compounds, such as phytoalexins, antimicrobial peptides, and pathogenesis-related proteins [ 135 , 136 ].…”
Section: Role Of Mel In the Mitigation Of Biotic Stressesmentioning
confidence: 99%
“…Furthermore, MT controls the AsA-GSH cycle, which is essential for ROS detoxification, and enzymes like APX, MDHAR, DHAR, and GR were involved in the regulation of this cycle [84]. Rehman et al [85] explained that MT effectively scavenges ROS by increasing the activity of the antioxidant enzyme glutathione peroxidase (GPX), which scavenges lipid peroxides, hydroperoxides, and H 2 O 2 under stress.…”
Section: Antioxidant or Ros Scavengingmentioning
confidence: 99%
“…OsDRP2B, a gene related to dynamin, was found to be mutated in rice at the brittle culm 3 mutant locus and is likely essential for clathrin-mediated endocytosis. OsCESA4 protein accumulation is reduced in rice culm 3 mutants, but OsDRP2B overexpression increases OsCESA4 protein accumulation in plasma membrane [120]. Proof for endocytosis emerged from in vitro and yeasttwo hybrid experiments that showed that CESA interacts with the medium subunit of ADAPTER PROTEIN COMPLEX 2 (AP2M) in clathrinmediated endocytosis.…”
Section: The Assembly and Localization Of Cscmentioning
confidence: 99%
“…Disorders in cell wall growth and the production of cytokinesis stubs have been found in mutants [131]. The cell plate accumulates CSLD5 in the form of punctate structures [132]. Mannans or xylans may be the cell wall substance that this enzyme generates [133].…”
Section: Transportation and Biosyn-thesis Of Non-cellulosic Polysacch...mentioning
confidence: 99%